Social capital and management innovation: The case studies of two Chinese Private SMEs - Lang, Qin (2014)
China’s small and medium-sized private enterprises play a vital role in promoting economic growth, technological progress and social development. This thesis investigates the survival environment of China’s small and medium-sized enterprises, discusses their responses to various market risks and systemic obstacles and more deeply explores why they have become the main drivers of Chinese economic growth. Firstly, this thesis systematically reviews the development history and relevant research of China’s small and medium-sized enterprises. Secondly it reviews theory on small enterprises’ corporate governance, social capital theory and incentive theory. Thirdly, we analyze two cases of Chinese private enterprises with the purpose to illustrate emerging problems, devise possible solutions and seek clarification from the theories reviewed. The first case concerns an entrepreneurial company set up by Mr. and Mrs. Y, a couple who has worked and studied abroad. The company is engaged in the pavement construction of highways and in the sale of relevant road high-tech materials. The second case concerns a poultry and pig-breeding enterprise built by a peasant family. The main conclusion of this thesis is that private enterprises in China not only have to deal with risks caused by industry, but also have to face policy volatility and overcome financing difficulties through social capital and social networks. In national capital monopolized sectors, policy volatility will make it hard for private enterprises to survive and social capital will be faced with limitations. So private enterprises have a larger room for development in industries where state capital is less prevailing. The key reasons for the rapid development of private enterprises in China have been innovation spirit and management innovation. This is the main innovation method of the above-mentioned two enterprises.